2021
DOI: 10.1371/journal.pone.0245995
|View full text |Cite
|
Sign up to set email alerts
|

Rebamipide ameliorates indomethacin-induced small intestinal damage and proton pump inhibitor-induced exacerbation of this damage by modulation of small intestinal microbiota

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) induce small intestinal damage. It has been reported that rebamipide, a mucoprotective drug, exerts a protective effect against NSAID-induced small intestinal damage; however, the underlying mechanism remains unknown. In this study, we investigated the significance of the small intestinal microbiota in the protective effect of rebamipide against indomethacin-induced small intestinal damage in mice. A comprehensive analysis of the 16S rRNA gene sequencing revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
8
0
4
Order By: Relevance
“…Interestingly, mice transplanted with feces from indomethacin-treated mice showed less intestinal injury and lower levels of proinflammatory cytokines when exposed to the NSAIDs, compared to the mice transplanted with feces from control groups (Xiao et al, 2017), and this result may be related to the adaptive beneficial changes in the gut microbiota. And Tanigawa et al reported that the transplantation of the small intestinal microbiota of the rebamipide-treated mice improved the small intestinal damage induced by indomethacin and omeprazole (Tanigawa et al, 2021). This observation suggested the potential role of FMT in the treatment of the NSAID enteropathy.…”
Section: Fecal Microbial Transplantationmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, mice transplanted with feces from indomethacin-treated mice showed less intestinal injury and lower levels of proinflammatory cytokines when exposed to the NSAIDs, compared to the mice transplanted with feces from control groups (Xiao et al, 2017), and this result may be related to the adaptive beneficial changes in the gut microbiota. And Tanigawa et al reported that the transplantation of the small intestinal microbiota of the rebamipide-treated mice improved the small intestinal damage induced by indomethacin and omeprazole (Tanigawa et al, 2021). This observation suggested the potential role of FMT in the treatment of the NSAID enteropathy.…”
Section: Fecal Microbial Transplantationmentioning
confidence: 98%
“…Tanigawa et al reported that in the rebamipide-treated mice, Lactobacillales increased while the abundance of Bacteroides and Clostridium subcluster XIVa decreased (Tanigawa et al, 2013). And it was reported that the administration of rebamipide decreased the concentration of Lactobacillus taiwanensis whereas increased the proportion of Lactobacillus murinus (Tanigawa et al, 2021). Meanwhile, increased expression of a-defensin 5, a critical anti-microbial peptide produced by Paneth cells was found in rebamipidetreated mice (Ouellette, 2004).…”
Section: Mucosal Protective Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To induce small intestinal injury, we administered IND (10 mg/kg, Sigma) in a 0.5% CMC solution by oral gavage to nonfasting mice. Twenty‐four hours later, the mice were sacrificed, and small intestinal injury was observed 10 …”
Section: Methodsmentioning
confidence: 99%
“…Twenty-four hours later, the mice were sacrificed, and small intestinal injury was observed. 10 The study was performed after the mice were allowed to acclimate for 1 week. Then, the mice were randomly divided into six groups (n = 5): the control group, model group, and four intervention groups.…”
Section: Induction Of Acute Small Intestinal Injury By Indomethacinmentioning
confidence: 99%